Formulation development, optimization and evaluation of Aloe vera gel for the management of post-harvest disease of mango anthracnose caused by Colletotrichum gloeosporioides (Penz.) Penz. & Sacc. - Theradimani, M; Senthil, K; Rajinimala , N; Sheela , J; Juliet, H S; Ayyandurai , M (Plant Science Today, 2025)
The Mango (Mangifera indica L.), one of the most economically important fruit crops, is produced predominantly in India, the world's leading mango producer. India grapples with anthracnose, a major farm and post-harvest disease that significantly limits mango production, particularly in high-humidity regions of India. The diseased mangoes collected from Kumbakarai, Periyakulam and nearby Madurai in Tamil Nadu, India, were used to identify a virulent strain of C. gloeosporioides through molecular analysis. Sequencing of the 560 bp PCR product yielded the GenBank Accession Number Ol468719. Phylogenetic analysis of the sequence showed 99 % identity with C. gloeosporioides sequences in the database. A. vera dry gels were prepared and diluted to concentrations of 10 %, 20 %, 30 %, 40 % and 50 % using potato dextrose agar medium. In vitro efficacy of different concentrations of A. vera gel against C. gloeosporioides was tested. Among the 10 %, 20 %, 30 %, 40 % and 50 % concentrations, significant inhibition was recorded at 10 %. Several antimicrobial compounds were identified from A. vera gel, including 1-dodecanol, 1-tetradecene, 1-hexadecanol, heneicosane, dibutyl phthalate and 1-heptacosanol, by GC-MS technique. An emulsifiable concentrate of A. vera gel was subsequently formulated and evaluated for its efficacy against the pathogen, offering a potential alternative approach for postharvest disease management.